1999
DOI: 10.1590/s0074-02761999000300012
|View full text |Cite
|
Sign up to set email alerts
|

Triatoma bassolsae sp. n. from Mexico with a key to species of "phyllosoma" complex

Abstract: Triatoma bassolsae sp. n. from Mexico with a key to species of "phyllosoma" complex -According to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…barberi # # Chickencoops and frequently in human houses (Lent and Wygodzinsky, 1979) Yes (Lent and Wygodzinsky, 1979) T. bassolsae # # Inside human houses and peridomestic environment (Aguilar et al, 1999) Yes (Aguilar et al, 1999) T. bolivari Sylvatic environments Martinez-Ibarra et al, 2010) Rarely found in peridomestic environment (MartinezIbarra et al, 2010) Yes (Martinez-Ibarra et al, 2010) T. boliviana Among rocks (Martínez Avendaño et al, 2007) Inside human houses and peridomestic environment (Martínez Avendaño et al, 2007) # #…”
mentioning
confidence: 99%
“…barberi # # Chickencoops and frequently in human houses (Lent and Wygodzinsky, 1979) Yes (Lent and Wygodzinsky, 1979) T. bassolsae # # Inside human houses and peridomestic environment (Aguilar et al, 1999) Yes (Aguilar et al, 1999) T. bolivari Sylvatic environments Martinez-Ibarra et al, 2010) Rarely found in peridomestic environment (MartinezIbarra et al, 2010) Yes (Martinez-Ibarra et al, 2010) T. boliviana Among rocks (Martínez Avendaño et al, 2007) Inside human houses and peridomestic environment (Martínez Avendaño et al, 2007) # #…”
mentioning
confidence: 99%
“…These characters were length of anteocular region (ARL: P<0.000), length of head excluding neck (HL: P < 0.000), length of first and second labial segments (Llb1: p < 0.03; Llb2: P < 0.001), and length of postocular region (PRL: P < 0.001) (Table 1). [7], Alejandre-Aguilar et al [32], and Rengifo-Correa et al [20]) 1. Pronotum with humeral angles acute.…”
Section: Morphometrymentioning
confidence: 99%
“…In 1930, it came to be considered a species of the genus Triatoma [20]. In 2000, it was classified in the genus Triatoma bassolsae was described in 1999 as a species of the genus Triatoma Laporte, 1832 [11]. In 2000, Carcavallo et al [12] suggested the reclassification of the species to the genus Meccus Stål, 1859, and recently Justi et al [7] and Cesaretto et al [13] demonstrated that it is a species of Triatoma.…”
Section: Introductionmentioning
confidence: 99%